2016
DOI: 10.1182/blood-2016-03-707562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of complete molecular response on survival in patients with Philadelphia chromosome–positive acute lymphoblastic leukemia

Abstract: • In patients with Ph 1 ALL, achievement of CMR at 3 months is independently associated with improved survival.• CMR at 3 months may identify patients with Ph 1 ALL who have excellent long-term outcomes without SCT in first CR.The impact of achieving complete molecular response (CMR) in Philadelphia chromosomepositive (Ph 1 ) acute lymphoblastic leukemia (ALL) remains undefined. We evaluated the impact of CMR on outcomes among 85 patients with Ph 1 ALL who received first-line hyperfractionated cyclophosphamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
179
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 16 publications
9
179
1
5
Order By: Relevance
“…In individual studies of chemotherapy plus a TKI, deeper molecular responses have been associated with improved survival . Similar findings also have been reported in pooled analyses of patients treated with chemotherapy plus one of several TKIs . In one report of patients with Ph+ ALL who did not undergo stem cell transplantation in first remission, the achievement of CMR at 3 months was found to be independently associated with improved OS and was associated with an impressive 4‐year OS rate of 66% .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In individual studies of chemotherapy plus a TKI, deeper molecular responses have been associated with improved survival . Similar findings also have been reported in pooled analyses of patients treated with chemotherapy plus one of several TKIs . In one report of patients with Ph+ ALL who did not undergo stem cell transplantation in first remission, the achievement of CMR at 3 months was found to be independently associated with improved OS and was associated with an impressive 4‐year OS rate of 66% .…”
Section: Discussionsupporting
confidence: 61%
“…In a phase 2 trial, chemotherapy with HCVAD plus ponatinib was found to be associated with a CMR rate of 78%, which is higher than that reported with other TKIs in combination with chemotherapy . Furthermore, previous studies have suggested that deeper molecular responses in patients with Ph+ ALL are independently predictive of improved survival …”
Section: Introductionmentioning
confidence: 85%
“…Studies suggest that the incorporation of TKI (imatinib) into the treatment regimen for Ph+ALL patients has led to improvements in outcomes over chemotherapy alone and, by increasing remission rates, may have lead to an increase in the percentage of patients preceding to AlloSCT (Thomas et al , ; Yanada et al , ; Fielding et al , ). A recent study showed excellent outcome for Ph+ALL patients who achieved complete molecular remission at 3 months with a combination of TKI and chemotherapy but without AlloSCT (Short et al , ). AlloSCT could potentially be restricted to patients who do not achieve a complete molecular remission or at the time of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…15 For Ph-negative ALL, MRD was assessed using 6-color multiparametric flow cytometry (MFC) analysis. 16 …”
Section: Methodsmentioning
confidence: 99%